A conceptual framework for determinants of the student advisory system at The University Of Nizwa Oman - Al-Anbari, Yaqoob Khamis; Khan, Nusratullah; Nusratullah, Kajal; Khan, Imran; Shah, Asadullah; Khedher, Akram M Z M; Mohamed Sofiadin, Aidrina; Abu Seman, Muhamad Sadry (IEEE Xplore, 2024)
Abstract—This study investigates the influence of the COVID-19 epidemic on implementing an automated student academic advice system at the University of Nizwa, with a specific emphasis on students' emotional intelligence. This study aims to determine the factors that may affect the usage of the automated student academic advisory system at the University of Nizwa in the Sultanate of Oman and to create a conceptual framework that illustrates the relationship between these factors and the utilization of the system. The researcher incorporates the literature review of the most pertinent article in this study, utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) model and employing a case study methodology. Data for pilot testing is gathered from a sample of 35 students and advisers. The initial data analysis was conducted using SPSS version 26. Based on the obtained results, the questionnaire utilized in this study is suitable for gathering additional data from participants. Furthermore, the study demonstrates that all the constructs chosen for this investigation exhibit reliability, as indicated by their Cronbach alpha test range falling inside the necessary threshold.